The International Standard Banking Practice for the examination of documents under documentary credits, ICC Publ. Nr. 645 - Goebel, Patrick (Department of Commercial Law, 2023)
The heart of this paper deals with the so-called "International Standard Banking Practice" (ISBP), its role in the world of documentary credits and in banking and trading business as a whole, its legal standing and its content. Despite the fact that the ISBP is expected to play an important role in the legal area of documentary credits, the ISBP has not yet been legally commented on in recognized academic legal circles. It is however an area that is significantly important enough to warrant examination and critique. This thesis is an attempt to make a contribution in this respect.